PENERAPAN PERMAINAN TRADISIONAL DALAM PEMBELAJARAN PENJAS UNTUK PEMBENTUKAN SIKAP FAIR PLAY SISWA - Fachdialy, Fachdialy; Firmansah, Yandri Driyana; Hardiyana, Hendri (STKIP Pasundan, 2018)
The problem that will be expressed in this research is: how big influence of traditional game in learning pemas to attitude of fair play student at SMK Pasundan 1 Cimahi . The goal is to find out how much influence the game in learning pemas to the fair play attitude of students . The population used in this study is an active class X students of the school, amounting to 69 people, with a random sampling technique. The research variables consist of one independent variable that is traditional game and one dependent variable that is attitude fairplay students . Instrument in this research, that is questionnaire of fair play attitude ofstudent . The method of research is experimental method . Data analysis used a percentage descriptiveanalysis . Based on the survey results revealed that the percentage value of honesty and sense of justice by89.71%, amounting to 88.14% passion play, respect for opponents of 88.88%, regulatory compliance by 90.57%, despite losing a big heart for 88% and humble in victory by 89.86% . So: From the results of these data can be concluded that the attitude of fair play students in the traditional game berdaasarkan research results more influential sub-sub-regulatory compliance.